Impact of Entrepreneurial Orientation, Job Satisfaction and Organizational Learning on Organizational Performance in MSME Rico Tempe Chips in Ngawi - Harits Nur Choiri; Ahmad Mardalis (Universitas Muhammadiyah Surakarta, 2025)
Purpose: Organizational performance is a systematic tool for assessing the success of a business, and the success of a business is directly proportional to the performance of employees within its organizational system. Factors that are thought to directly influence organizational performance within a organizational are entrepreneurial orientation, job satisfaction, and organizational learning.Methodology: In this study, the method used is a quantitative method using a questionnaire as a data collection method. The sampling technique used is purposive sampling. The analysis used in this study is a descriptive multivariate regression analysis using the SPSS statistical application. Results: The results of the study indicate that the variables of entrepreneurial orientation, job satisfaction, and organizational learning have a positive and significant effect on organizational performance, as evidenced by the significance coefficient of the three variables being below 0.05 and the T-test value for the three variables has more value than Ttabel (2.037).